HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG TOILET TRAINING DENGAN TINGKAT KEMANDIRIAN BALITA DALAM TOILETING DI POSYANDU ASTER I SONOPAKIS KIDUL YOGYAKARTA - Yuli Ernawati; Suri Salmiyati (STIKES Wira Husada Yogyakarta, 2018)
Background : Parents have a strategic role in the development of children under ﬁ ve years old. The ability of toddlers that need to be achieved is independence in toileting. Successful toileting skills require the anticipatory guidance of parents as one of the stimulation of parenting to the child. This study aims to determine whether there is a relationship between mother’s knowledge level of toilet training with the independence’s level of toddlers in toileting at Posyandu Sonopakis Kidul Yogyakarta.Method: It is a quantitative research with cross sectional design to mother who have toddler in Posyandu Aster I Sonopakis Kidul Yogyakarta with purposive sampling technique. The instrument was a questionnaire. Statistical test using Chi Square test to analyze the relationship between two variables. Results: 22 respondents (73.33%) had a good level of knowledge about toilet training, 20 toddlers (66.67%) have independence in toileting. The relationship between mother’s knowledge about toilet training with the level of independence of toddlers in toileting obtained results p value = 0.010Conclusion: There is a relationship between mother’s knowledge level about toilet training with independence level of toddler in toileting